2021
DOI: 10.1101/2021.01.22.21250304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rates of serious clinical outcomes in survivors of hospitalisation with COVID-19: a descriptive cohort study within the OpenSAFELY platform

Abstract: BackgroundPatients with COVID-19 are thought to be at higher risk of cardiometabolic and pulmonary complications, but quantification of that risk is limited. We aimed to describe the overall burden of these complications in survivors of severe COVID-19.MethodsWorking on behalf of NHS England we used data from the OpenSAFELY platform linking primary care records to death certificate and hospital data. We constructed two cohorts: a COVID-19 cohort consisting of patients discharged following hospitalisation with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…Separately numerous cohort studies have reported an increased risk of serious cardiovascular and metabolic outcomes following hospitalisation with COVID 8,9 , and there are various prospective studies such as the Post-hospitalisation COVID-19 study (PHOSP) following up hospitalised patients over the next year 10 . Other studies have examined variation in clinical coding, with some finding that "poor" coding can lead to altered incidence estimates 11 , while others implicate the design of clinical software systems in influencing variation [12][13][14] .…”
Section: Research In Contextmentioning
confidence: 99%
“…Separately numerous cohort studies have reported an increased risk of serious cardiovascular and metabolic outcomes following hospitalisation with COVID 8,9 , and there are various prospective studies such as the Post-hospitalisation COVID-19 study (PHOSP) following up hospitalised patients over the next year 10 . Other studies have examined variation in clinical coding, with some finding that "poor" coding can lead to altered incidence estimates 11 , while others implicate the design of clinical software systems in influencing variation [12][13][14] .…”
Section: Research In Contextmentioning
confidence: 99%
“…Auch im Vergleich zu Patienten mit durchgemachter Influenza-Pneumonie zeigen COVID-19-Patienten ein um ca. 30-50 % erhöhtes Risiko für Myokardinfarkte und Schlaganfälle in der post-akuten Phase[101]. Die Inzidenz neu auftretender kardiovaskulärer Komplikationen in den ersten 6 Monaten nach COVID-19 ist direkt assoziiert mit dem Schweregrad der Akuterkrankung.…”
unclassified
“…The ONS COVID Infection Survey estimates prevalence of self-diagnosed long COVID at 13.7% 6 . Separately numerous cohort studies have reported an increased risk of serious cardiovascular and metabolic outcomes following hospitalisation with COVID 7,8 , and there are various prospective studies such as PHOSP following up hospitalised patients over the next year 9 .…”
Section: Discussionmentioning
confidence: 99%